Analysis of Eco-Friendly Cafe in Jambi City - Erlangga, Erlangga; Syarifuddin, Hutwan; Harmes, Harmes (Rifa'Institute, 2025)
Introduction: Eco-friendly cafes are a concern in supporting sustainable tourism. This study examines cafes in Jambi City based on Permenparekraf No. 10 of 2014 and the Green Practice concept. Purpose: to analyze the suitability of the implementation of cafe business standards and environmentally friendly principles that cover aspects of products, services, management, as well as Green Action, Green Food, and Green Donation. Method: The study used the Stratified Simple Random Sampling method with Proportional Allocation, involving 30 out of 150 cafes in Jambi City. Data analysis was conducted quantitatively with the Compliance Checklist and Importance Performance Analysis (IPA). Result and Discussion: The results show that the product aspect has been implemented very well, while the service and management aspects still need to be improved, especially in the management, HR, and infrastructure indicators. The IPA conformity value of 91.66% indicates quite good performance. Of the 40 attributes analyzed, 4 attributes from Green Action and Green Donation require special attention, while Green Food has been implemented very satisfactorily. . Conclusion: The implementation of environmentally friendly principles in cafes in Jambi City is quite good, but there is still room for improvement, especially in terms of service, management, and certain green practices.